‘Change for the Better?’: Making sense of housing association mergers in the Netherlands and England - van Bortel, Gerard; Mullins, David; Gruis, Vincent (A+BE | Architecture and the Built Environment, 2016)
Mergers among housing associations have become a frequent phenomenon in both the Netherlands and England. The general literature on mergers highlights the need for research to consider the wider political and business environment, managerial motives and strategic choices, to adopt a process perspective and to evaluate outcomes in relation to competing definitions of goals and success criteria. This article applies these perspectives to consider drivers for and experience of housing association mergers in the Netherlands and England, competing motivations such as efficiency savings in relation to borrowing and procurement costs, improved professionalism and organisational capacity and external influence. We discuss the pace and motivations of mergers, the expected positive and negative effects, and actual outcomes. We focus on the impact of mergers on stakeholder satisfaction, housing production and operational costs. Based on our findings we discuss the implications for policies and practice in both countries. Our main conclusion is that the relationship between the size of housing associations and their performance is not straightforward. This is partly because large and small associations are generally trying to do different things in different ways and have contrasting strengths and weaknesses; thus judgements about whether mergers and concentration of ownership in third sector housing is a change for the better are dependent upon considerations of underlying purposes and success criteria.